Evaluation of a Muslim Pre-School in the United States Using Elements of the Ofsted Model - Hassan Elannani (National University of Modern Languages (NUML), Islamabad, 2023)
This article reviewed the Ofsted inspection model in England and reported on its implementation in a Muslim pre-school located in an American southeastern state. The inspection methods included classroom observations, interviews with staff, parent survey, and scrutiny of artifacts. After the pre-school was inspected and the feedback was given to the administration orally and in a detailed written report, an improvement plan was developed by the author to address the inspection recommendations. The results of the inspection showed that implementing elements of the Ofsted inspection model in the pre-school contributed to overall educational improvement. A follow-up communication with the administration showed that curriculum changes were made, teachers were provided with more professional development opportunities, and their teaching practices had improved. Considering these findings, this study demonstrated that there was an alignment between the mission of the pre-school and the parents' aspirations; and that an educational accountability system such as the Ofsted inspection model have had a positive impact on the educational provision even though not all elements of the inspection model were implemented, many of which require a team of inspectors and a quality assurance mechanism.